2023
DOI: 10.3390/computers12080153
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Implementation of ChatGPT in Education: A Systematic Review

Marta Montenegro-Rueda,
José Fernández-Cerero,
José María Fernández-Batanero
et al.

Abstract: The aim of this study is to present, based on a systematic review of the literature, an analysis of the impact of the application of the ChatGPT tool in education. The data were obtained by reviewing the results of studies published since the launch of this application (November 2022) in three leading scientific databases in the world of education (Web of Science, Scopus and Google Scholar). The sample consisted of 12 studies. Using a descriptive and quantitative methodology, the most significant data are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Several previous studies indicated the potential utility of ChatGPT as a prime example among other LLMs in higher education 1,18,26,[63][64][65] . For example, Montenegro-Rueda et al highlighted the potential for ChatGPT to facilitate the interaction between students and teachers besides being a motivational tool in the learning process 26 . In a relevant editorial, Meyer et al pointed out that the main issue regarding LLMs' use in academia would be approach by which students employ these models 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies indicated the potential utility of ChatGPT as a prime example among other LLMs in higher education 1,18,26,[63][64][65] . For example, Montenegro-Rueda et al highlighted the potential for ChatGPT to facilitate the interaction between students and teachers besides being a motivational tool in the learning process 26 . In a relevant editorial, Meyer et al pointed out that the main issue regarding LLMs' use in academia would be approach by which students employ these models 63 .…”
Section: Discussionmentioning
confidence: 99%
“…ChatGPT, while intended for conversational assistance, has been appropriated for diverse purposes, from drafting legal and academic documents to creating artistic compositions [1][2][3][4][5]. The recontextualization of technology, while innovative, surfaces inherent risks.…”
Section: Introductionmentioning
confidence: 99%
“…The application of ChatGPT extends well beyond its initial conception, echoing a common narrative in the evolution of technology where tools are repurposed in manners unforeseen by their creators. ChatGPT, while intended for conversational assistance, has been appropriated for diverse purposes, from drafting legal and academic documents to creating artistic compositions [1][2][3][4][5]. The recontextualization of technology, while innovative, surfaces inherent risks.…”
Section: Introductionmentioning
confidence: 99%
“…Constructed on the GPT-3.5 architecture, ChatGPT is a language model proficient in comprehending and producing text that closely resembles human language, contingent on the provided user input . Its ability to understand context, generate coherent responses, and mimic natural language has garnered tremendous attention across diverse domains, including education …”
mentioning
confidence: 99%
“…9 Its ability to understand context, generate coherent responses, and mimic natural language has garnered tremendous attention across diverse domains, including education. 10 ChatGPT may be of utility for chemists and educators for a variety of applications. 11 Several recent reports have investigated ChatGPT's viability as a calculation, 12 quiz, 13 or problem solving tool.…”
mentioning
confidence: 99%